Economic design of variable sampling interval sign control chart. (19th May 2017) - Patil, S. H.; Shirke, D. T.
Abstract: In this article, we have proposed an economic design of variable sampling interval (VSI) control chart based on sign statistic. An expression for expected loss per unit time is obtained and minimized with respect to design parameters. The performance of this economic design is compared with economic design of fixed sampling interval (FSI) sign chart to control location of process characteristic. Though the power of VSI sign chart is slightly lower than that of FSI sign chart design, it appears to be dominant over FSI sign chart design for moderate shifts. The effect of change in input parameters on loss cost is observed for different out of control probabilities of quality characteristic under VSI sign chart scheme. Change in shift parameter, penalty cost parameter, and time to detect the shift have considerable effect on loss cost from the design. The design is fairly robust to the changes in other parameters.